2018
DOI: 10.1155/2018/5198594
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐Inflammatory Effects of p‐Coumaric Acid, a Natural Compound of Oldenlandia diffusa, on Arthritis Model Rats

Abstract: Objectives In China, Oldenlandia diffusa (OD) is a natural herb that is widely used and has been proven to be effective in the treatment of rheumatoid arthritis (RA). This study aimed to preliminarily reveal the mechanism by which OD exerts its beneficial effect. Methods Ultra-performance liquid chromatography photodiode array was applied to identify the absorbable compounds in the plasma of collagen-induced arthritis (CIA) model rats. After 2 weeks, an OD decoction or the identified absorbable compound was ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(32 citation statements)
references
References 42 publications
3
28
0
Order By: Relevance
“…41 The results of the determination of 19 phenolic metabolites showed growth year-specific properties, with the C 6 C 3 -type metabolites mainly accumulated in 3-year-old plants, the C 6 C 1 -type in 9-year-old plants, and the C 6 C 3 C 6 -type in 5-year-old plants. p-Coumaric acid is said to have antioxidant, 42 anti-inflammatory, 43 and neuroprotective effects. 44 The results showed that pcoumaric acid accumulated mainly in the 3-year-old plants.…”
Section: Discussionmentioning
confidence: 99%
“…41 The results of the determination of 19 phenolic metabolites showed growth year-specific properties, with the C 6 C 3 -type metabolites mainly accumulated in 3-year-old plants, the C 6 C 1 -type in 9-year-old plants, and the C 6 C 3 C 6 -type in 5-year-old plants. p-Coumaric acid is said to have antioxidant, 42 anti-inflammatory, 43 and neuroprotective effects. 44 The results showed that pcoumaric acid accumulated mainly in the 3-year-old plants.…”
Section: Discussionmentioning
confidence: 99%
“…MAPK activation leads to phosphorylation of CREB gene in RNA which results in decreased expression of BDNF [ 44 ]. Further, anti-inflammatory and analgesic effects of p-CA are quite remarkable in several diseases such as diabetes, gout and arthritis, while p-CA has various bioactivities [ 45 46 ]. Its anti-inflammatory and analgesic effects were not inferior to drug such as indomethacin [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the in vivo study of intraperitoneal administration of ferulic acid in the Balb/c mice upregulation of antioxidant protection and suppression of inflammatory responses via the inhibition of TLR-4 induced activation of nuclear factor kappa B (NF-κB) was observed, which indicates the potential use of ferulic acid for protection against sepsis-induced acute kidney injury [ 171 ]. p -Coumaric acid, as one of the active ingredients in the Chinese natural herb Oldenlandia difusa , showed anti-inflammatory activity via the suppression of inflammatory cell infiltration as well as the levels of TNF-α and IL-6, which are known as pro-inflammatory factors that can activate the NF-κB signaling pathway, thereby increasing the inflammatory response and have an important role in the pathogenesis of rheumatoid arthritis [ 172 ]. Similarly, in another study p -coumaric acid exhibited considerable anti-inflammatory activity in vivo in arthritic rats via reduction of TNF-α expression in synovial tissue and circulating immune complexes in serum [ 173 ].…”
Section: Biological Activities and Health Benefits Of Hcas And Thementioning
confidence: 99%